Loving The Domestic Product As A Manifestation Of State Defense In Global Era - Siswanto, Siswanto (Jurnal Pertahanan dan Bela Negara, 2017)
Abstract – The background of this paper is the fact of social, economical, and political change of Indonesian in the Reform and global era. It Includes changes in the context of defending state which in the past it was understood only as a military activity. The defending of state nowadays has a broader meaning in economic, social, and cultural context. The defending of state in the context of economy is more commitment to consume national products than to consume foreign product. Therefore, the purpose of this paper is to analyze the problems of defending the state in the economic context that involves people's habits of favoring foreign products, the impact of consumption patterns on selecting external products to foreign exchange reserves, and strategies that can be built to make people prefer national products. The method used in this paper is literature study that is studying references or previous studies related to this issue, and in-depth discussion with relevant sources. This has been done to confirm or improve an understanding the topic being written. The results of this studies are in the form of conclusions and recommendations to build the pattern of public consumption to prefer national products rather than foreign products. Keywords: state defense, national product, foreign product